An economical and safe procedure to synthesize 2-hydroxy-4-pentynoic acid: A precursor towards ‘clickable’ biodegradable polylactide - Zhang, Quanxuan; Ren, Hong; Baker, Gregory L. (Beilstein Journal of Organic Chemistry, 2014)
2-Hydroxy-4-pentynoic acid (1) is a key intermediate towards ‘clickable’ polylactide which allows for efficient introduction of a broad range of pendant functional groups onto polymers from a single monomer via convenient ‘click’ chemistry with organic azides. The incorporation of various pendant functional groups could effectively tailor the physicochemical properties of polylactide. The reported synthesis of 1 started from propargyl bromide and ethyl glyoxylate. However, both of starting materials are expensive and unstable; especially, propargyl bromide is shock-sensitive and subjected to thermal explosive decomposition, which makes the preparation of 1 impractical with high cost and high risk of explosion. Herein, we report a simple, economical and safe synthetic route to prepare 1 using cheap and commercially available diethyl 2-acetamidomalonate (4) and propargyl alcohol. The desired product 1 was obtained via alkylation of malonate 4 with propargyl tosylate followed by a one-pot four-step sequence of hydrolysis, decarboxylation, diazotization and hydroxylation of propargylic malonate 5 without work-up of any intermediate.
Keywords: alkylation; ‘click’ chemistry; ‘clickable’ polylactide; decomposition; diethyl 2-acetamidomalonate; 2-hydroxy-4-pentynoic acid; one-pot; optimization; propargyl bromide; propargyl tosylate; safe and economical